Trade and innovation in the Middle East and North Africa - Ficarra, Matteo,Gökten, Meryem,Harasztosi, Péter,Lesma, Roberta,Pál, Rozália,Weiss, Christoph,Koczan, Zsoka (European Investment Bank, 2022)
Participation in international trade goes hand-in-hand with innovation in the private sector in the Middle East and the North Africa, according to data collected from 6 000 companies. International trade is a key determinant of the competitiveness and innovation of firms in the Middle East and North Africa. In Egypt, Jordan, Lebanon, Morocco, Tunisia and the West Bank and Gaza, firms that trade in international markets tend to innovate more, and trade grows faster when the firms invest in innovation. Trade with developed economies and access to information and know-how through participation in international markets can help firms in the Middle East and North Africa catch up with other regions and close the innovation gap. Improving customs and trade regulations can increase access to international markets to a larger share of firms. The Enterprise Surveys, conducted by the EIB, EBRD and the World Bank, provide insight into what lies beneath the region's relatively slow growth, with a focus on the reasons for stagnating productivity and inadequate accumulation of human and physical capital in the private sector. This is the sixth of nine working papers supporting the full report: Unlocking sustainable growth in the Middle East and North Africa private sector.
10.2867/423250
Keywords: Graue Literatur; Trade; firm performance; business environment; COVID-19; innovation; international trade; private sector; competitiveness; access to information; know-how; market; Arab world